Medicinal trees of Hazaribag district, Jharkhand, India (International Journal of Food and Nutritional Sciences, 2022)
This study contributes to knowledge of medicinal trees of Hazaribag district, Jharkhand, India. Thegoal of the research of medicinal trees was to learn more about the folklore around plant remedies. Themajority of the territory is rich in plant diversity, and the residents of the economically disadvantagedvillages of Hazaribag district primarily rely on agriculture and wild resources to meet their dailyrequirements. This document includes a list of 48 medicinal trees from 23 families and 41 genera. Thebotanical names, vernacular names, their respective family names, part of the plant used and their usesare indicated. Fabaceae was the dominant family followed by Moraceae, Meliaceae, Apocynaceae,Combretaceae, Euphorbiaceae, Myrtaceae, Rutaceae, Verbenaceae, Anacardiaceae, Annonaceae,Bignoniaceae, Boraginaceae, Lauraceae, Lythraceae, Moringaceae, Musaceae, Oleaceae, Rhamnaceae,Rubiaceae, Salicaceae, Sapotaceae, and Tiliaceae. The observations are based on local folklore andinterview of various communities and tribes of the Hazaribag district. Therefore, the ethnobotanicalknowledge of people and listing of plants of particular region are important tools that help inunderstanding human environment interactions.